Corrigendum to: Nomenclatural changes allow for a broadened circumscription of Lophogyne Tul. to reflect a prominent neotropical clade of Podostemaceae (Podostemoideae) - Bove, Claudia P.; Philbrick, C. Thomas; Da Costa, Filipe G.c.m. (Phytotaxa, 2019)
The new name, Lophogyne royenella C.P.Bove & C.T.Philbrick, is proposed to replace the illegitimate later homonym Lophogyne capillacea (Tul.) C.T.Philbrick & C.P.Bove.